Joint user grouping and antenna selection based massive MIMO beamforming - Qian WANG; Quan HUA; Yingchao ZHOU; Bin SHEN (Dianxin kexue)
In massive MIMO systems，when the number of users is larger as that of antennas at base station（BS），the various channels may be significantly different.A new zero-forcing beamformer design algorithm was proposed based on joint user grouping and antenna selection for massive MIMO dowlink systems.All users were divided into two groups and then the group of users with a better channel condition was selected to receive signal with selecting an optimal antenna combination for each transmit data stream，in order that RF circuit cost and power consumption could be reduced substantially with a little loss of performance in massive MIMO systems.The simulation results show that the proposed algorithm provides a better trade-off between rate performance and hardware complexity in massive MIMO system.